2011
DOI: 10.2478/s11536-011-0046-9
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure induced itai-itai-like syndrome in male rats

Abstract: AbstractFourteen Sprague-Dawley male rats were randomly divided into 2 groups which were given CdCl2 at the doses of 0 and 1.5 mg /kg for 12 weeks. Before sacrifice, microCT scanning were performed on the proximal tibia and urine were collected for cadmium and N-acetyl-beta-D-glucosaminidase assay, then all of rats were sacrificed and blood was collected for biomarkers measurement; bone tissues were collected for bone mass, histology and biomechanical analysis. The cadmium in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(50 reference statements)
2
3
0
Order By: Relevance
“…This indicates a disruption in the growth of the Cd-exposed rats. These results are consistent with the findings of Chen et al [19], which indicated a decrease in the body weight of Sprague Dawley rats that were subcutaneously injected with a dosage of 5 mg/kg of Cd. This study also confirms the findings of Yousef et al which demonstrated a significant reduction in the body weight of laboratory rabbits that were administered a dosage of 5 mg/kg of oral Cd for one month [35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates a disruption in the growth of the Cd-exposed rats. These results are consistent with the findings of Chen et al [19], which indicated a decrease in the body weight of Sprague Dawley rats that were subcutaneously injected with a dosage of 5 mg/kg of Cd. This study also confirms the findings of Yousef et al which demonstrated a significant reduction in the body weight of laboratory rabbits that were administered a dosage of 5 mg/kg of oral Cd for one month [35].…”
Section: Discussionsupporting
confidence: 93%
“…rats increased slightly (9%) but the body weight of the other two control treated rats increased significantly (P ≤ 0.05) at the end of the experimental period. Chen et al [19] indicated a decrease in the body weight of male Sprague Dawley rats treated with cadmium at a dose of 1.5 mg/kg body weight. Rabbits treated with oral dose of 5 mg cadmium/kg b.w.…”
Section: Effects Of Cadmium Selenium and Lycopene On Body Weightmentioning
confidence: 99%
“…[21] or by malabsorption of nutrients from the gastrointestinal tract f Cd-treated rats as reported by [40]. Similar results were observed by Chen et al [41] which indicated a decrease in the body weight of Sprague Dawley rats that were subcutaneously injected with a dosage of 5 mg/kg of Cd. Other finding also demonstrated a significant decrease in the body weight of rabbits that were administered a dosage of 5 mg/kg of oral Cd for one month [42] [43].…”
Section: Effect Of Treatments On Bone Dna Aspectsupporting
confidence: 83%
“…Previously, Cd-induced bone damage was thought to be mediated through renal dysfunction such that primary damage is done to the kidneys and damage to the bones is a secondary effect [87]. However, in this study, the authors suggest that Cd intoxication can have a direct impact on the bone such that renal dysfunction and altered bone formation and reabsorption is caused simultaneously in relation to the dose of Cd exposure [86]. Another study showed histopathological alteration in bone marrow of albino Wistar rats treated with 15 mg Cd/kg b.w.…”
Section: Cadmium-induced Tissue Injurymentioning
confidence: 63%
“…A study by Chen et al reported severe damages to the proximal tibia of male Sprague Dawley rats treated with 1.5 mg Cd/kg b.w. for 12 weeks inducing Itai-itai-like syndrome [86]. Authors reported a 20% -50% decrease in bone mineral density along with 30% -60% decrease in bone biomechanical property.…”
Section: Cadmium-induced Tissue Injurymentioning
confidence: 97%